2004
DOI: 10.1007/s00535-004-1354-5
|View full text |Cite
|
Sign up to set email alerts
|

Reg protein is a unique growth factor of gastric mucosal cells

Abstract: In 1984, Reg protein was shown to be stimulated during the regeneration of pancreatic islets. Since then, many Reg-related proteins have been identified in humans and other animals. These Reg-related proteins are classified into four subfamilies according to their amino-acid sequences, but they share a similar structure and physiological function. The role of Reg in gastric tissue was investigated, and Reg I was found to be expressed mainly in gastric fundic enterochromaffin-like (ECL) cells. Reg I production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 32 publications
1
41
1
Order By: Relevance
“…Reg I is an acinar cell-derived product of the pancreas, is constitutively expressed and secreted from the acinar cells, and can be ectopically induced within regenerating islets. Reg I protein is an established mitogen to pancreatic β-, ductal and mucosal cells of the GI tract including the stomach and colon (2,(4)(5). We have shown that purified recombinant reg I is bioactive as well (6), and is mitogenic to primary cultures of ductal cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Reg I is an acinar cell-derived product of the pancreas, is constitutively expressed and secreted from the acinar cells, and can be ectopically induced within regenerating islets. Reg I protein is an established mitogen to pancreatic β-, ductal and mucosal cells of the GI tract including the stomach and colon (2,(4)(5). We have shown that purified recombinant reg I is bioactive as well (6), and is mitogenic to primary cultures of ductal cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many Reg-related genes have been isolated and shown to constitute a multigene family (types I-IV) (8). We have previously reported that REG I␣ and REG IV are involved in the pathophysiology of GI inflammation (5,17) and that, moreover, they act as trophic and/or antiapoptotic factors under inflammatory conditions (17,18).…”
mentioning
confidence: 99%
“…2,3 Recently, many Reg-related genes have been isolated and shown to constitute a multigene family. 4 Among human REG family proteins, REG Ia and REG IV are reportedly overexpressed in a subset of gastric cancer. [5][6][7][8][9] Moreover, several microarray analyses have recently isolated REG Ia and REG IV as novel genes that are overexpressed in gastric cancer tissues, 10,11 suggesting that both genes have important functions in gastric carcinogenesis.…”
mentioning
confidence: 99%